Análisis de la cartera de créditos periodo 2019 de la Cooperativa de Ahorro y Crédito San Antonio Agencia Mata de Cacao - Prieto Zuñiga, Vanessa Kristel (2020)
This study focused on the loan portfolio of the Coopertiva de Ahorro y Crédito San Antonio LTDA. Agency Mata de Cacao period 2019, the San Antonio cooperative is a financial intermediation institution that aims to contribute to the development of the community in order to improve the quality of life. The análisis to be carried out is to the loan portfolio becuase it has had several problems such as the increase in delinquency which caused the unproductie portfolio to increase, these consequences occurred because the loan personnel did not follow the policies of the institution,the agents at granting the credit does not accurately analyze the partner and ther ability to comply with the payment of said credit, that is whyat the time of canceling the debt the partners do not comply with their obligation. The análisis of the loan portfolio Will be carried out through different financial reassons, the delinquency index that affects the recovery of the porfolio, according to numerical data, the agency Mata de Cacao has the loan portfolio with the highest delinquency at comparación of the other agencies and parend company. The superintendency of the popular and solidarity economy determines that the liquidity index Will measure the level that the institution has to meet is obligations. The techniques that Will be used are observation, interview and bibliographic review, the inductive method, deductive method and analytical method were applied, the line of research to be used is management of accounting information.